The Effect of Cerebral Small Vessel Disease on the Subtypes of Mild Cognitive Impairment - Li, Xudong; Shen, Miaoxin; Jin, Yi; Jia, Shuhong; Zhou, Zhi; Han, Ziling; Zhang, Xiangfei; Tong, Xiaopeng; Jiao, Jinsong (Frontiers in Psychiatry, 2021)
Objectives: Cerebral small vessel disease (CSVD) is the most common vascular cause of dementia and mild cognitive impairment (MCI) is an intermediate state between dementia and normal cognitive aging. The present study investigated the main imaging features of CSVD on different MCI subtypes in memory clinics. Methods: A total of 236 patients with MCI and 85 healthy controls were included. One hundred nine amnestic MCI-multiple domains (amMCI), 38 amnestic MCI-single domain (asMCI), 36 nonamnestic MCI-multiple domains (namMCI), and 53 nonamnestic MCI-single domain (nasMCI) patients were diagnosed. All participants were evaluated with the cognitive assessments and imaging features including white matter hyperintensity (WMH), enlarged perivascular spaces (EPVS), cerebral microbleeds (CMBs), and cerebral atrophy according to a standard procedure. Results: The patients with amMCI, namMCI and nasMCI had more high-grade basal ganglia EPVS compared with healthy controls, while the percentages of high-grade basal ganglia EPVS in the patients with amMCI were also more than those in patients with asMCI, namMCI and nasMCI. There were more high-grade centrum semiovale EPVS in patients with amMCI in comparison with all other groups. The patients with amMCI and namMCI had more percentages of severe deep and periventricular WMH and deep CMBs compared with healthy controls. All MCI groups had higher scores of the medial temporal lobe atrophy than healthy controls, whereas the scores of amMCI group were also higher than those of namMCI and nasMCI groups. Conclusions: There were varied neuroimaging features of CSVD including cerebral atrophy in different MCI groups, which meant that vascular mechanism contributed to the prodromal stage of dementia.